Efeito de uma intervenção com vídeo games ativos nos fatores de risco para síndrome metabólica e no estilo de vida em adultos com Síndrome de Down - Kalinoski, Angelica Xavier (2013)
The Down Syndrome (DS) is a genetic accident classified as intellectual deficit. Some people with DS have associated diseases, which together with a non-active lifestyle, leaves them susceptible to develop a number of chronic non-communicable diseases. Some of these diseases are risk factors for Metabolic Syndrome, such as glucose intolerance, insulin resistance or diabetes mellitus, including two or more factors such as hypertension, elevated plasma triglyceride, HDL and central obesity. It is necessary to increase physical activity for this population. The aim of this study was to investigate the effects of a physical activity program with exergaming (Xbox 360 ® kinectTM), during 16 weeks, on the variables of the Metabolic Syndrome. Physical fitness related to performance tests were conducted and the sessions intensity was controlled usingGT3X accelerometers. It is an experimental study and the population consisted of people with Down syndrome, both sexes over 18 years, residents of the city of Pelotas - RS. We identified 44 individuals, 28 have accepted to participate in the study meeting the inclusion criteria. The sample consisted of 28 subjects, divided into two groups (G1 - intervention (N = 14) and G2 - control (N = 14)), randomly selected and matched by sex. The intervention lasted 16 weeks with 3 sessions per week for 50 minutes. Were applied before and after the intervention a life style questionnaire, physical fitness performance tests, verified hemodynamic variables and conducted biochemical analyzes of both groups. For statistical analysis we used the statistical package SPSS 20.0 for Windows. Regarding Metabolic Syndrome variables systolic blood pressure was the only factor that presented significant difference p <0.01 compared to groups in the post test. In motor performance tests the experimental group presented statistically significant difference in strength tests of upper limb, lower limb strength and agility test showing a p <0.01 when compared between groups, upper limbs strength test was statistically significant. Regarding intensities during the session the overall average was 17.3 minutes in light activity, 22.2 minutes in moderate activity and 10.5 minutes in vigorous activities. Therefore we see a need for accessible programs, health promotion strategies and interventions to increase physical activity levels of people with disabilities. An alternative is to use exergaming that besides being motivational activities are activities with intensities that can change significantly variables related to health.